Analisis Faktor-Faktor yang Mempengaruhi Gangguan Perilaku dan Fungsi Kognitif di Masa Pandemi COVID-19 Pada Pasien Poliklinik Neurologi RSUD dr. Zainoel Abidin - Suherman; Fitria Armalivia; Ika Marlia (Journal of Medical Science, 2022)
COVID-19 pandemic is an extraordinary issue and attacks almost the entire world population. Mental health problems such as behavioral disorders and cognitive disorders that arise as a result of the pandemic can develop into health problems that can last long time and potential to cause heavy social burden. This study aims to analyze factors that influence behavioral and cognitive function disorders during COVID-19 pandemic in patients at Neurology Outpatient Clinic RSUD dr. Zainoel Abidin. This study used a descriptive-analytic research method with a cross-sectional design. Bivariate data were analyzed using t-test. Totaled participants during July−September 2022 was 122 respondents, consisting of males (n=68) and females (n=54). Based on Moca Ina score’s result, respondents aged <40 years (14.8%), higher education level (24.6%), had no history of chronic disease ( 25.4%), and have coping skills (27%) showing normal cognitive function. Based on Abe's BPSD score’s result, higher education level (26.2%) and coping abilities (24.6%) show normal behavior. Age, level of education, history of chronic disease, and coping abilities are associated with impaired cognitive function, while educational level and coping abilities are associated with behavioral disorders.